Ambient Pressure Tympanometry Wave Patterns in Patients With Superior Semicircular Canal Dehiscence - Thai, Anthony; Sayyid, Zahra N.; Hosseini, Davood K.; Swanson, Austin; Ma, Yifei; Aaron, Ksenia A.; Vaisbuch, Yona (Frontiers in Neurology, 2020)
Importance: Superior semicircular canal dehiscence (SSCD) is a treatable condition, but current diagnostic modalities have numerous limitations. Clinicians would benefit from an additional tool for diagnostic workup that is both rapid and widely available. Objective: To assess the utility of ambient pressure tympanometry (APT) in the diagnostic workup of SSCD by determining the sensitivity and specificity of APT for SSCD in comparison to other diagnostic modalities. Design: Retrospective cohort study of patients who underwent APT and temporal bone computerized tomography (CT) scans from May 2017 to July 2018. Setting: Tertiary referral center. Participants: APT was performed as part of routine audiological testing on adult patients. We retrospectively analyzed all patients who received both APT and temporal bone CT scans, and divided ears into SSCD and non-SSCD groups based on the presence or absence of radiographic SSCD. Ears with other radiographic findings that could affect tympanic membrane compliance were excluded. Exposures: All patients in this study underwent APT and temporal bone CT scans. Some patients also underwent pure tone audiometry and vestibular evoked myogenic potentials (VEMPs). Main Outcomes and Measures: The primary outcome measures were sensitivity, specificity, and risk ratio of APT for SSCD. Secondary outcome measures include sensitivity of VEMPs and supranormal hearing thresholds. Results: We describe 52 patients (70 ears) who underwent APT and CT imaging (mean age 47.1 years, 67.1% female). APT detected SSCD with 66.7% sensitivity and 72.1% specificity. In symptomatic patients, sensitivity was 71.4% and specificity was 75%. VEMPs performed best at detecting SSCD when defining a positive test as oVEMP amplitude >17 uV, with a sensitivity of 68.2%, similar to APT (p>0.99). The combination of APT and VEMPs increased sensitivity to 88.9%, better than APT alone (p=0.031) and trending toward better than VEMPs alone (p=0.063). Conclusions and Relevance: Rhythmic wave patterns on APT are associated with SSCD and may raise suspicion for this condition in conjunction with consistent results on other diagnostic modalities. Although clinical utility requires confirmation in a larger prospective study, APT is a simple, rapid and widely available tool warranting further study.